2015
DOI: 10.1007/s11051-015-3020-7
|View full text |Cite
|
Sign up to set email alerts
|

IrPd nanoalloys: simulations, from surface segregation to local electronic properties

Abstract: SSCI-VIDE+ECI2D+LPIInternational audienceUsing semi-empirical modeling, namely tight-binding at different levels of accuracy, the chemical, crystallographic, and electronic structures of bimetallic IrPd nanoparticles are characterized. For the purpose, model cuboctahedral particles containing 561 atoms are considered. Atomistic simulations show that core-shell nanoparticles are highly stable, with a strong surface segregation of Pd, at least for one atomic shell thickness. Within self-consistent tight-binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Moreover, unlike Pd nanoparticles, PdIr nanoalloys do not form a β -hydride phase. Consistently with previous TEM-EDX analyzes which have suggested a surface enrichment in Pd 6 , computational simulations for small clusters 10 and 2 nm-sized particles 11 predict various chemical configurations mostly driven by a strong surface segregation of Pd and the large miscibility gap of bulk PdIr, which has profound consequences on surface reactivity 12,13 .…”
Section: Introductionsupporting
confidence: 82%
“…Moreover, unlike Pd nanoparticles, PdIr nanoalloys do not form a β -hydride phase. Consistently with previous TEM-EDX analyzes which have suggested a surface enrichment in Pd 6 , computational simulations for small clusters 10 and 2 nm-sized particles 11 predict various chemical configurations mostly driven by a strong surface segregation of Pd and the large miscibility gap of bulk PdIr, which has profound consequences on surface reactivity 12,13 .…”
Section: Introductionsupporting
confidence: 82%
“…Beyond downsizing, nanoalloying is an additional way of boosting the hydrogen absorption capacity, as shown for Pd-Pt and Ag-Rh systems [160]. In contrast, we have found that nanoalloying Pd with Ir strongly decreases the hydrogen absorption capacity of Pd and suppresses β hydriding [161,162] through the formation of a core-shell Ir@Pd structure (Figure 7, left-hand side) [163,164]. The decreased hydrogen capacity is correlated to a strongly increased preferential CO oxidation activity in the presence of H 2 (PROX process) with respect to pure Pd and Ir counterparts [161,165].…”
Section: Hydrogen Absorption and Hydridingmentioning
confidence: 73%
“…23,24 Pd-Ir nanoalloys are often used as catalysts in the preferential oxidation of CO (PROX). 8,10 The Pd-Ir system has rarely been studied computationally, [25][26][27][28][29] and relatively few catalytic studies have been devoted to Pd-Ir nanoalloys. 9,27,30 In this study, the structure and chemical ordering of bare and CO-adsorbed Pd-Ir nanoalloys have been investigated theoretically by using density functional theory (DFT).…”
Section: Introductionmentioning
confidence: 99%